CHEMICAL PROCESSES AND UV-C IRRADIATION FOR PHENOL REMOVAL IN INDUSTRIAL WASTE STREAMS - Sumaiya Azam1, Nabeela Kanwal2, Anirudh Gupta3, Dr. Shayan Zufishan5, Dr. Syeda Asiya Parveen6, Ali Imran Mallhi7 (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Industrial processes generate substantial amounts of complex waste materials, necessitating the removal of contaminants before disposal. Phenolic compounds, particularly concerning due to their harmful effects on human health and the environment, are prevalent byproducts in various industrial activities, such as gasoline processing.Objective: This study aims to investigate the primary factors influencing the reduction of phenolic compounds and their conversion into minerals through chemical processes.Methods: The original waste discharge, characterized by a pH of approximately 7, containing 5 g L-1 of sand (containing TiO2) and 22 mg L-1 of oxidizing hydrogen peroxide. The reduction process was monitored over 60 minutes, during which the total phenol content decreased by approximately 90%. Phenol levels were measured using an ultraviolet spectrophotometer employing the standard 4-amino antipyrine method at a wavelength of 510 nm. Reactions took place in a reactor equipped with a 95 W UV-C lamp for sterilization.Results: The reduction process achieved a substantial decrease in phenol content within the specified timeframe. The use of UV-C light facilitated efficient degradation, leading to a notable reduction in phenolic compounds.Conclusion: Understanding the factors influencing phenol reduction in industrial waste is crucial for effective waste management strategies. This study highlights the efficacy of chemical processes coupled with UV-C irradiation in mitigating phenol pollution, offering a promising approach for environmental remediation efforts.